Classed trajectories in higher education and the graduate labour market: affective affinities in a 'meritocracy'. Issue 8 (9th December 2022) - Bunn, Matthew; Burke, Penny Jane; Threadgold, Steven
Abstract: In this article, we draw from a recent empirical study to consider how a person's classed trajectory impacts students from different class backgrounds in higher education (HE). Students face rapidly evolving social and academic circumstances and must build reasonable strategies to navigate their trajectory from education to work. In these situational processes, social class becomes emotionally exposed as a durable relational social ordering principle. Affinities with educational and labour market norms provide emotional advantages. To explore the classed nature of accumulated being in Australian HE in the context of widening participation, we examine experiences of access to and participation in HE, and strategies towards entry into the labour market. The movement into, through and out of HE orders and organises classed experience, demonstrating the durability of class in the face of doxic meritocratic choice discourse.